PEMELIHARAAN IKAN NILA DENGAN PADAT TEBAR BERBEDA PADA BUDIDAYA SISTEM AKUAPONIK - Juardi Zalukhu; mirna fitrani; Ade Dwi Sasanti (Jurnal Akuakultur Rawa Indonesia, 2016)
ABSTRACT Aquaponic is a farming system that use water continuously from fish rearing to the plant and conversely. Aquaponic system aims to reduce the level of ammonia produced by fish feces and feed waste then maintain oxygen level in recycling water through an existing system. Determination of the optimal stocking density in aquaponic will ensure the best survival and growth of fish. The research was conducted since March to April 2016 at the Laboratory of Aquaculture, Aquaculture Study Program, Faculty of Agriculture, Sriwijaya University, Indralaya. This research used a completely randomized design (CRD) with four treatments with three replications of stocking density 100, 150, 200, dan 250 fish/m2. Based on observations during the study, the highest percentage for survival rate was 84.67% (P2=150 fish), whereas growth for the highest percentage of both absolute weight and lenght were 1.42 g and 1.52 cm (P1=100 fish), however there were no significan differences between P1 dan P2. Plant growth data show that the best growth was in P3 (200 fish). Based on research results, P2 (150 fish) wassugested to apply for the tilapia in aquaponic system. Â  Key words : Aquaponic,Tilapia, Stocking density